Odpowiedzi

2010-03-27T12:44:28+01:00
Najlepsza Odpowiedź!
2010-03-27T12:45:04+01:00
A. 4x-3=3x+5
4x-3x=5+3
x=8
b. 5x+2=7-3x
5x-3x=7-2
2x=5 /2
x=5/2
x=2,5
c. 3( x -1)=0
3x-3=0
3x=0+3
3x=3 /3
x=1
d. -6(x+1)=24
-6x-6=24
-6x=30 /(-6)
x=-5
e. -7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15 /(-10)
x=15/10
x=1,5
f. 4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10 /(-2)
x=-5



2 5 2
2010-03-27T13:40:35+01:00
A. 4x-3=3x+5
4x-3x=5+3
x=8

b. 5x+2=7-3x
5x+3x=7-2
8x=5
x=5/8

c. 3( x -1)=0
3x-3=0
3x=3
x=1

d. -6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30
x=-5

e. -7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15
x=15/10=3/2

f. 4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10
x=-5
1 5 1